'Being normal' and self-identity: the experience of volunteering in individuals with severe mental disorders—a qualitative study. Issue 3 (23rd March 2019) - Pérez-Corrales, Jorge; Pérez-de-Heredia-Torres, Marta; Martínez-Piedrola, Rosa; Sánchez-Camarero, Carlos; Parás-Bravo, Paula; Palacios-Ceña, Domingo
Abstract : Objective: This study sought to explore the views and experiences of a group of people with severe mental disorders (SMDs) who performed volunteer services. Design: A qualitative phenomenological study. Setting: Community public mental health services of the Community of Madrid and the province of Barcelona (Spain). Participants: Purposive sampling techniques were used between September 2016 and April 2017. The inclusion criteria were: individuals aged 18–65 years who participated in volunteer activities during the performance of this study, based on the regulations of volunteer services in Spain and the community of Madrid; a diagnosis of non-organic psychotic disorder (F20.x, F21, F22, F24, F25, F28, F29, F31.x, F32.3 and F33) according to the International Classification of Diseases, 10th Revision; an evolution of ≥2 years; and a moderate to severe dysfunction of global functioning with scores ≤70 in the Global Assessment of Functioning Scale. Ultimately, 23 people with SMD participated in the study with a mean age of 47 years (SD 8.23). Methods: Data were collected through in-depth interviews and researcher field notes. A thematic analysis was performed following appropriate guidelines for qualitative research. Results: Two main themes emerged to describe the experience of participating in volunteer activities: (1) rebuilding self-identity, based on the participant's experience of volunteering, of acquiring a new role and a new perceived identity that made them feel valued and respected; and (2) being a so-called normal person with a 'normal' life, based on recovering a sense of normality, unmarked by the illness, thanks to daily responsibilities and occupations. Conclusions: Qualitative research offers insight into the way people with SMD experience volunteering and may help to improve understanding of the underlying motivations that drive these individuals. These findings may be applied to improve guidance during their process of recovery and subsequent inclusion into society.